Upaya RSUD Dr. Fauziah Bireuen Meyakinkan Masyarakat Tentang Vaksinasi Covid-1 - Nadia Zahara Putri; Dhiya Aula Fillah (Sadida Islamic Communications and Media Studies, 2021)
This study entitled "The efforts of the RSUD dr. Fauziah Bireuen to convince the public to be willing to be vaccinated against COVID-19". One of the efforts of dr. Fauziah Bireuen Hospital to fight Covid-19 is to hold vaccinations for all people in Bireuen district. However, these efforts have encountered problems with the many negative opinions from the public regarding the Covid-19 vaccination. Some people still refuse vaccines, due to doubts about the safety and short and long-term side effects of the vaccine itself. This research is a descriptive research with quantitative and qualitative approaches. The data collection technique uses a survey from Google forms related to the receipt of covid-19 vaccination in a number of people in Bireuen district and interviews against one of the health workers from the RSUD dr. Fauziah Bireuen is Ns. Ismaidah,S.Kep. The purpose of the research or writing of this article is to find out the efforts of RSUD dr. Fauziah Bireuen to convince the public to be willing to be vaccinated against COVID-19. The results showed, There are 45 respondents from the people of Bireuen Regency who are willing to vaccinate against COVID-19 and 5 respondents who are not willing to vaccinate against COVID-19. Therefore, various strategies, methods, and periodic socialization are also carried out so that the public can understand well the importance of vaccination and also the effectiveness of the covid-19 vaccine, so that they can provide information and increase public confidence in the covid-19 vaccine.